Etomidat versus Propofol zur Anästhesie bei ambulanter Kardioversion - Kick, O.; Böhrer, Hubert; Motsch, Johann; Keßler, Jens; Conradi, Renate; Martin, Eike (Anästhesiologie, Intensivmedizin, Notfallmedizin, Schmerztherapie, 1996)
Thieme E-Books & E-Journals